FED BATCH PHYTOREMEDIATION REGIME FOR ENHANCED NUTRIENT REMOVAL BY SALVINIA MOLESTA ON FISH FARM WASTEWATER (ASEAN Engineering Journal, 2022)
Phytoremediation is a bioremediation process that uses various types of plants to remove, transfer, stabilize, and destroy contaminants in the soil and groundwater. In this study, the performance of fed batch (FB) phytoremediation by S. molesta on fish farm wastewater was investigated by varying percentage of fresh wastewater loading. This study was aimed to investigate the biomass production of S. molesta through different FB percentage cultivation along with nutrient removal aiming to treat wastewater. The water quality after phytoremediation was monitored throughout 16 days. The nutrient removal efficiency was high in higher percentage of FB but all the medium achieved standard discharge limit. Ammonia and phosphate removal showed very high (˂95%) for 75% FB medium with total removal of 46.59 mg and 5.46 mg respectively. The removal of ammonia and phosphate by control set was 13.73 mg and 1.62 mg. Although the concentration of nitrate continued to increase throughout the study, FB cultivation minimized the increment where all percentage experienced decrease in nitrate value and 75% FB had lowest level of 2.40 mg/L compared to control which was 5.00 mg/L. However total nitrogen value in higher FB medium indicated highest value of 13.85 mg/L on day 16. VSS for FB medium was far below control. FB phytoremediation of S. molesta in fish farm water showed high efficiency in nutrient removal but no significant effect on its biomass. This study proved that FB phytoremediation of S. molesta has potential on nutrient removal from fish farm wastewater